2016
DOI: 10.24200/jeps.vol10iss4pp680-686
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Emotion Regulation Strategies as Predictors of Academic Achievement among University Students

Abstract: Abstract:The purpose of this study was to investigate the impact of cognitive emotion regulation strategies on academic achievement of university students in Jordan. A random sample of 386 students from the Hashemite University participated in the current study. The Cognitive Emotion Regulation questionnaire was used to measure the cognitive emotion regulation strategies. The findings of this study showed that cognitive emotion regulation strategies had significant joint effect and relative effect on academic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Furthermore, some other studies support the findings of the present study. For example, Al-badareen found that emotion regulation strategies affect students' academic achievement (28). In another study, Hafiz et al showed that emotion regulation and related strategies play a positive role in increasing students' academic performance (29).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some other studies support the findings of the present study. For example, Al-badareen found that emotion regulation strategies affect students' academic achievement (28). In another study, Hafiz et al showed that emotion regulation and related strategies play a positive role in increasing students' academic performance (29).…”
Section: Discussionmentioning
confidence: 99%